Analgesic Efficacy of Bupivacaine or Bupivacaine-Dexmedetomidine After Intraperitoneal Administration in Cats: A Randomized, Blinded, Clinical Trial - Benito, Javier; Evangelista, Marina C.; Doodnaught, Graeme M.; Watanabe, Ryota; Beauchamp, Guy; Monteiro, Beatriz P.; Steagall, Paulo (Frontiers in Veterinary Science, 2019)
The aim of this study was to compare the analgesic efficacy of intraperitoneal bupivacaine versus bupivacaine-dexmedetomidine in combination with buprenorphine in cats undergoing ovariohysterectomy. Sixty healthy adult cats (2.8 ± 0.7 kg; n = 30/group) were included in a randomized, prospective, blinded, clinical trial after owners’ written consent. After premedication with acepromazine (0.02 mg/kg) and buprenorphine (0.02 mg/kg) intramuscularly, anesthesia was induced with propofol to effect (6.2 ± 1.4 mg/kg) and maintained with isoflurane. Bupivacaine 0.25% alone (BG; 2 mg/kg) or bupivacaine (same dose) with dexmedetomidine (BDG; 1 µg/kg) were instilled/splashed over the ovarian pedicles and caudal aspect of the uterus before ovariohysterectomy. Final injectate volume was standardized between groups. Sedation was evaluated using a 5-point simple descriptive scale. Pain was evaluated using the short-form UNESP-Botucatu composite pain scale (SF-CPS) before, and at 0.5, 1, 2, 3, 4, 6, 8, 12 and 24h after surgery. Rescue analgesia was provided with buprenorphine (0.02 mg/kg intravenously) and meloxicam (0.2 mg/kg subcutaneously) when SF-CPS ≥ 4. The Mantel-Haenszel chi-square test was used for analyzing ordinal variables (e.g. SF-MCPS pain scores). The effect of time in SF-CPS scores was assessed with the Cochran-Mantel-Haenszel test for repeated measures. The alpha level for each contrast was adjusted downward with the sequential Benjamini-Hochberg procedure. The number of cats receiving rescue analgesia was analyzed using χ2 test (p < 0.05). The prevalence of rescue analgesia was the same for the two treatments (p = 1.000; [BG, n = 6, 20%; BDG, n = 6, 20%] and similar for timing of rescue analgesia (p = 0.16). The SF-CPS scores were significantly increased between 1 and 12h in BG, and between 0.5 and 8h in BDG when compared with baseline values. Median (interquartile range) pain scores were higher in BG [1(1-21.38 ± 0.9)] than BDG [1(0-10.80 ± 0.8)] at 12h (p = 0.023). Sedation scores were not significantly different between groups throughout the study. In terms of prevalence of rescue analgesia, but not duration of action, the analgesic efficacy of bupivacaine-dexmedetomidine was similar to bupivacaine alone after intraperitoneal administration in cats receiving buprenorphine.